Thermal profiles of amorphous solid dispersions (ASD) in 3D printed tablets by fused deposition modelling (FDM): Production of tunable tablet doses - Heba Iqbal (17337667) (2025)
Conventionally, manufactured tablets do not provide flexibility for personalizing dosing to patients. Furthermore, most Active Pharmaceutical Ingredients (APIs) suffer from poor solubility. We aimed to simultaneously address these two constraints through application of amorphous solid dispersions (ASD) and additive manufacturing such as Fused Deposition Modelling (FDM) using ibuprofen (IBU) as model drug. The ASD displayed a porous microstructure, with ibuprofen transformed from crystalline to amorphous state and a complete loss of the melting point. Aptly, there was a 35% increase in solubility and a significant increase (p < 0.05) in dissolution rates of ibuprofen from 3D printed ASD tablets compared to printed tablets of pure ibuprofen. It was also possible to modify the dissolution profile of ibuprofen based on changes in the dimensions of the ASD tablets, thereby providing scope for tuning doses for specific patient needs. Other Information Published in: Thermal Advances License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.thradv.2025.100027